Pengaruh Latihan Agility Ladder Exercise Terhadap Kemampuan Dribbling Pada Atlet Sepak Bola KU 13-15 Tahun Di Sekolah Sepak Bola (SSB) Putra Sawerigading Rante Limbong - Muhammad Indra Arif, Edy Basri, Basman (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
The purpose of this study was to determine how much to know the effect of Agility Ladder Exercise training on dribbling ability in 13-15year old soccer athletes at the Sawerigading Rante Limbong Male Soccer School (SSB). The population in this study was Population is the entire research subject